Barron's TOEIC® : test of English for international communication - Lougheed, Lin, Dr.; First news. (Tp.HCM : Nxb. Tổng hợp, 2012)
1. Introduction; 2. Listening Comprehension; 3. Reading; 4. TOEIC Model Tests.
Keywords: English language; English language -- Vocabulary; TOEIC -- Test